Improvement of geometric product specification through a priori evaluation of uncertainty of CMM measurements - Mauricio de Campos Porath and Theo Hageney and Hendrik Mietzner (Measurement: sensors, 2025)
Designers often define geometric specifications without considering the measurement uncertainty of the inspection processes because this information is not available. A new method - called the VCMM-User method - that allows such an a priori evaluation of the task-specific measurement uncertainty of coordinate measurements is now available. This method, based on Monte Carlo simulations, is described and measurement uncertainties are evaluated for several characteristics of a specific artifact. These uncertainties are verified using an established method. The sensitivity of the method to alternative specifications was demonstrated. Plausibility of the measurement uncertainty values could by verified by comparison with an established method.
Keywords: Coordinate measuring machine (CMM); Measurement uncertainty; Geometric product specification (GPS); Virtual CMM (VCMM); Monte Carlo simulations